Inhibition of Mico.nazole –resistant mutants o’f Candida al:J,lcalts; by aqueous extract of Matric aria chamomile
fhe .rudy has shad a light on the abi_ lity Qf aq,ueous. extract of Mairlr:aria chamomile ibr eliminating growth of miconazole. .resistant muta.nt of Candida albkÂ·afzy. whi-ch i:,solated from . human. ruiil and vagina ;Tfl- inimJ.tJTI inhibition cohc!:lhtra_tion (MIC) is l6 Jrl’g/n: l. Spon-taneous tesistant .mutatiqns-.fot mic-onazole were also is:ola ed by using sp 1-f.g/ml of rni:comlzoJeThis ::onc ntrf